Situação de rua e evasão escolar: atenção para a educação inclusiva - Lima, Andréia Barbosa de [UNESP]; Capellini, Vera Lúcia Messias Fialho [UNESP] (My University, 2011)
This paper aims to present a study about the importance of Education as a public policy for the integral development of children and adolescents in street situation. As theoretical foundation, the authors used constructs from the National Policy of Special Education in the perspective of Inclusive Education, the Statute of the Child and Adolescent emphasizing the importance of family and social networks as a way to protect children and adolescents who left school and live under the precarious situation of street. In this sense, the National Policy of Special Education in the perspective of Inclusive Education has just pointed to the issues that pass by the inclusion of these children and adolescents to put them back to school. To do this, it is necessary to implement policies designed to the care of children and adolescents victimized by the living on the streets.

Este trabalho objetiva apresentar um estudo sobre a importância da Educação enquanto política pública para o desenvolvimento integral de crianças e adolescentes em situação de rua. As autoras utilizaram-se dos construtos teóricos sobre a Política Nacional de Educação Especial na Perspectiva da Educação Inclusiva, o Estatuto da Criança e do Adolescente, dando ênfase à importância das redes sociais e da família, como forma de proteção à criança e ao adolescente, que se encontram em situação de rua, evadidos do âmbito escolar. Nesse sentido, a Política Nacional de Educação Especial na Perspectiva da Educação Inclusiva pouco tem apontado para as questões que perpassam a inclusão dessas crianças e adolescentes novamente na Escola, fazendo-se necessária a implementação de políticas voltadas para o atendimento de crianças e adolescentes vitimizados pela vivência de rua.
Situation in street and school evasion: atention for inclusive education
Keywords: Education; Social exclusion; Public policies; Support network; Educação; Exclusão social; Políticas públicas; Rede de apoio